Porous copper oxide catalyst as well as preparation method and application thereof
By combining metal salts with carbonizable organic matter matrix, a copper oxide catalyst with a porous structure is formed, and the problems of high catalyst density and low CuO utilization in the prior art are solved, and a low density, high activity and low cost catalyst is achieved.
Patent Information
- Application Number
- CN202311079329.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-25
AI Technical Summary
In the prior art, the porous composite copper oxide catalyst has a high density and the utilization rate of CuO is low, which cannot meet the requirements of industrial catalytic reactions for low-density and high-active catalysts.
Metal salts are used as raw materials to form smaller particles by calcining and high temperature decomposition, and foam them in the carbonizable organic matter matrix to form a porous structure, thereby reducing the density of the catalyst.
The density of the catalyst is reduced, the utilization rate and activity of the catalyst is improved, the cost is reduced, and the service life of the catalyst is extended.
Smart Images

Figure BDA0004413758660000101 
Figure BDA0004413758660000102
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and more particularly to a porous copper oxide catalyst and a preparation method and application thereof. Background Art
[0002] In various industrial fields, the presence of trace CO is often harmful to the reaction system or the safety of the system and needs to be removed as an impurity. In the polyolefin industry in the electronics industry and petrochemical field, the content of carbon monoxide and oxygen in the material flow is required to be even at the ppb level. With the development of the ethylene industry, the purity of the ethylene materials entering the polymerization refining section is getting higher and higher. The inlet CO in the process parameters proposed by many manufacturers is even less than 1ppm, and even less than 0.5ppm. The existing technology for removing trace CO mainly uses copper oxide catalysts prepared by coprecipitation method, which are cylindrical particles. The copper oxide inside the particles actually only plays a supporting role and fails to catalyze oxidation reaction with CO. That is to say, the CuO in the catalyst only plays a catalytic role in a small amount, and a large amount of CuO only plays a supporting role. The utilization rate of CuO is very low, that is to say, the activity of copper in the unit mass catalyst is not high. Due to the low utilization rate of CuO, many existing catalysts cannot meet the requirements of the process. In addition, the catalyst prepared by the tableting method usually has a higher density due to the preparation process. In industrial catalytic reactions, the demand for catalysts is in units of volume, so reducing the density of the catalyst can effectively reduce the mass of the catalyst. In other words, under the premise of the same removal capacity, reducing the density of the catalyst can not only effectively improve the catalytic activity of the catalyst per unit mass, but also effectively reduce the cost. Beijing Research Institute of Chemical Industry has developed a composite copper oxide catalyst, which is obtained by combining Raney copper with porous carbon and then oxidizing it. Compared with industrial copper oxide catalysts, the composite copper oxide catalyst improves the utilization rate of copper, but the copper-aluminum alloy in the center only plays a supporting role, and the improvement in reducing the catalyst density is not obvious.
[0003] Therefore, it is necessary to develop a porous copper oxide catalyst with lower density, which can effectively reduce the cost of the catalyst while improving the utilization rate of the catalyst. Summary of the invention
[0004] In order to solve the technical problems existing in the prior art, the present invention provides a porous copper oxide catalyst and a preparation method and application thereof.
[0005] The present invention uses metal salt as raw material. After roasting, the metal salt is decomposed into smaller particles. Compared with alloy particles as raw materials, the particle size is smaller and the density is lower. At the same time, the gas generated during the decomposition of the metal salt foams in the carbonizable organic matrix, causing the carbonized organic matter to become looser and form a porous structure, which can further reduce the density of the catalyst.
[0006] Compared with the porous composite copper oxide catalyst of the prior art, the preparation method of the catalyst of the present invention further simplifies the operation process. The catalyst after high temperature decomposition has no central component that only serves as a support but is inactive, and the entire catalyst has catalytic activity, and the method effectively reduces the density of the catalyst.
[0007] The porous alumina prepared by the conventional method is mainly prepared by the tableting method, and the obtained catalyst has a small specific surface area and a large density. The catalyst prepared by the present invention has a low density, a lower metal content while achieving the same catalyst activity, and a lower metal content of the catalyst of the same volume, thereby improving the utilization rate of the catalyst while reducing the cost of the catalyst, overcoming the problem of low utilization rate of the catalyst CuO obtained by the tableting method in the prior art, and being able to achieve the removal of trace CO.
[0008] One of the objects of the present invention is to provide a porous copper oxide catalyst.
[0009] The porous copper oxide catalyst has a porous structure and a density of 0.5 to 1.5 g / cm 3 , preferably 0.5 to 1.0 g / cm 3 , more preferably 0.5 to 0.8 g / cm 3 , with a specific surface area of 60 to 180 m 2 / g, preferably 120 to 180 m 2 / g.
[0010] In a preferred embodiment of the present invention,
[0011] The porous copper oxide catalyst is regenerated by air oxidation after its activity decreases or deactivation; preferably,
[0012] The oxidation temperature is 60 to 120°C; and / or,
[0013] The heating time is 3 to 48 hours, preferably 10 to 24 hours.
[0014] The second object of the present invention is to provide a method for preparing a porous copper oxide catalyst, comprising the following steps:
[0015] (1) uniformly mixing a metal salt with a solidification system of a carbonizable organic matter and then solidifying the mixture to obtain a catalyst precursor; the metal comprises copper;
[0016] (2) Under the protection of protective gas, the catalyst precursor obtained in step (1) is carbonized at high temperature to obtain the porous copper oxide catalyst.
[0017] In a preferred embodiment of the present invention,
[0018] Step (1),
[0019] The mass ratio of the metal salt to the carbonizable organic matter in the solidification system is (0.1-5):1, preferably (0.2-2):1, and more preferably (0.2-0.6):1;
[0020] The solidification system of the carbonizable organic matter comprises the carbonizable organic matter and an additive.
[0021] In a preferred embodiment of the present invention,
[0022] The metal salt is at least one of nitrate, carbonate and bicarbonate;
[0023] The metal also includes at least one of zinc, manganese and magnesium;
[0024] The mass of copper accounts for no less than 50% of the total mass of the metal, preferably no less than 60%.
[0025] In a preferred embodiment of the present invention,
[0026] The carbonizable organic matter refers to: treating the organic matter under certain temperature and atmosphere conditions, so that hydrogen, oxygen, nitrogen, sulfur, etc. in the organic matter are completely or partially volatilized, thereby obtaining a synthetic material with a high carbon content, and the obtained carbon material has the properties of high temperature resistance, high strength, high modulus, and porosity; the carbonizable organic matter is an organic polymer compound; preferably at least one of epoxy resin, phenolic resin, furan resin, polystyrene, polyacrylonitrile, starch, viscose fiber, lignin, cellulose, styrene-butadiene rubber, and polyurethane rubber;
[0027] The additives include a curing agent, and preferably also include at least one of a curing accelerator, a dye, a colorant, an antioxidant, a stabilizer, a plasticizer, a lubricant, a flow modifier, a flame retardant, an anti-drip agent, an anti-caking agent, an adhesion promoter, a conductive agent, an impact modifier, a demoulding aid, and a nucleating agent; the additives can specifically adopt the conventional additives in the art, and a suitable curing agent and an optional curing accelerator can be selected according to the different carbonizable organic matter. The dosage of the additives also adopts the conventional dosage in the art and is adjusted according to the actual requirements.
[0028] Mixing can be carried out by a common mixing method in the art, such as stirring;
[0029] The curing conditions also adopt the conventional curing conditions in the art, such as curing at 100-200° C., normal pressure-10 MPa, and 5-240 min.
[0030] After carbonization, the oxide particles are distributed in the gaps of the carbon. The porous carbon structure effectively disperses the metal oxide particles, which reduces the sintering of the metal oxide particles as much as possible during the high-temperature reaction, effectively increasing the service life of the catalyst. In addition, during the carbonization and sintering process, the carbonized organic polymer decomposes to form pores, resulting in a fluffy ultra-light structure. At the same time, the metal salt will also produce a large amount of gas during the decomposition process, which further expands the pores of the composite catalyst.
[0031] In a preferred embodiment of the present invention,
[0032] Step (2),
[0033] The protective gas is at least one of nitrogen and an inert gas; the inert gas is preferably argon; and / or,
[0034] The carbonization temperature is 400 to 1200° C.; preferably 400 to 700° C., more preferably 550 to 700° C.; and / or,
[0035] The carbonization time is 1 to 10 hours, preferably 2 to 6 hours, and more preferably 2 to 4 hours.
[0036] The third object of the present invention is to provide a porous copper oxide catalyst obtained by the above preparation method.
[0037] A fourth object of the present invention is to provide an application of a porous copper oxide catalyst in a reaction for removing trace amounts of CO.
[0038] In a preferred embodiment of the present invention,
[0039] The CO content in the material is 0.01 to 1000 ppm, preferably 0.01 to 100 ppm, more preferably 0.01 to 10 ppm, and most preferably 0.1 to 5 ppm;
[0040] The reaction temperature is 0 to 150°C, preferably 20 to 120°C;
[0041] The reaction pressure is 0.1 to 5 MPa, preferably 0.1 to 3.5 MPa;
[0042] The volume space velocity during gas phase reaction is 100~10000h -1 ;
[0043] The volume space velocity during liquid phase reaction is 0.5~100h -1 ;
[0044] When removing trace amounts of CO, the CO in the material flow after removal is less than 0.1 ppm, preferably less than 60 ppb, and more preferably less than 20 ppb. When the CO content in the material is relatively high, the method of the present invention is also suitable for removal. However, when the CO content in the material is relatively high, the concentration of CO in the material flow after removal will be slightly higher accordingly.
[0045] In a preferred embodiment of the present invention,
[0046] The material is at least one of α-olefins, saturated hydrocarbons, styrene, and other materials; the other materials are preferably at least one of hydrogen, nitrogen, oxygen, air, and inert gases; the material is preferably at least one of liquid materials of propylene, 1,3-butadiene, 1-butene, and 2-butene, or at least one of gaseous ethylene, gaseous propylene, hydrogen, nitrogen, oxygen, air, and inert gases.
[0047] In view of the fact that the heat released by the removal of trace amounts of S, O2, As and Cl is extremely small, single copper catalysts are often used to remove these impurities, and the catalyst disclosed in the present invention can also be applied in these fields.
[0048] The contents involved in the present invention, such as %, ppm and ppb, are all based on weight.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] (1) The present invention uses metal salt as raw material, which decomposes into smaller particles after calcination. Compared with alloy particles as raw materials, the particle size is smaller and the density is lower. At the same time, the gas generated during the decomposition of the metal salt foams in the carbonizable organic matrix, which makes the carbonized organic matter looser and forms a porous structure, which can further reduce the density of the catalyst. Therefore, the catalyst prepared by the present invention has a low density, and the mass of the catalyst per unit volume is about 2 / 3 of the mass of the catalyst prepared by the traditional tableting method.
[0051] (2) The catalyst prepared by the present invention has a low density. While achieving the same catalyst activity, the metal content is lower. The metal content of the catalyst of the same volume is less, which improves the utilization rate of the catalyst while reducing the cost of the catalyst. Compared with the porous alumina prepared by the tableting method in the prior art, the utilization rate of the catalyst metal oxide is higher.
[0052] (3) The preparation method of the present invention allows carbon to isolate the copper oxide active component, thereby preventing the excessive growth of copper oxide nanoparticles and reducing the CO removal capacity, thereby effectively extending the life of the catalyst.
[0053] (4) The catalyst of the present invention has a low reaction temperature, a simple preparation process, and is easy to load and unload. DETAILED DESCRIPTION
[0054] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0055] The raw materials used in the examples are all conventional commercially available raw materials.
[0056] Test method:
[0057] Density: The laboratory determination method is bulk ratio, using a measuring cylinder to measure and weigh 100 mL of catalyst.
[0058] Pore volume and specific surface area: measured using BET adsorption instrument.
[0059] Metal oxide content in the catalyst: X-ray fluorescence spectroscopy (XRF) was performed using an X-ray photoelectron spectrometer from PA Nalytical BV of the Netherlands. The elemental composition and relative content of the sample surface were analyzed after vacuuming.
[0060] Example 1
[0061] (1) 100 parts by weight of liquid epoxy resin (Baling Petrochemical, CYD-128), 85 parts by weight of curing agent methyltetrahydrophthalic anhydride (MeTHPA) (Guangdong Shengshida Science and Trade Co., Ltd.), and 1.5 parts by weight of curing accelerator triethanolamine (TEA) (Tianjin Chemical Reagent Factory No. 1) were stirred evenly.
[0062] (2) Weigh 125 g of the epoxy system prepared in step (1) and 33 g of copper nitrate, stir and mix them thoroughly, take an appropriate amount of the mixture and add it to a cylindrical mold, press it with a flat plate vulcanizer at a temperature of 120° C. and a pressure of 7 MPa for 30 mins, and press it with a flat plate vulcanizer at a temperature of 150° C. and a pressure of 7 MPa for 90 mins, cool it and take it out to obtain a cylindrical catalyst precursor of about 2.0 mm×3.0 mm;
[0063] (3) 100 ml of catalyst precursor was measured and placed in a tubular high-temperature electric furnace. The temperature was raised at a rate of 10 °C / min, the carbonization temperature was 650 °C, and the temperature was maintained for 3 hours. The nitrogen protection was at a nitrogen flow rate of 200 mL / min. After cooling under nitrogen protection, an ultra-light copper oxide catalyst was obtained with a density of 0.56 g / cm 3 , copper oxide content is 33.1wt%, specific surface area is 152m 2 / g.
[0064] Example 2
[0065] (1) Powdered phenolic resin and curing agent hexamethylenetetramine are fully mixed with a high-speed stirrer, and the weight ratio of hexamethylenetetramine to phenolic resin is 12 / 100; 125 grams of the mixture are fully mixed with a mixture of 33 grams of copper nitrate and 9 grams of zinc nitrate with a high-speed stirrer;
[0066] (2) raising the temperature of the tablet press to 90° C., placing the above materials into a mold and performing molding on the tablet press to form a 2 mm thick sheet; raising the temperature of the tablet press to 150° C., placing the formed sheet into the mold again and curing it under a pressure of 5 MPa on the tablet press for 10 min; cutting the cured 2 mm thick sheet into 3-5 mm rectangular small particles to obtain a catalyst precursor;
[0067] (3) 100 mL of the small particle catalyst precursor was measured and carbonized in a tubular high temperature electric furnace at a heating rate of 10 °C / min and a furnace temperature of 600 °C for 2 hours. The nitrogen protection was at a flow rate of 200 mL / min. After cooling under nitrogen protection, an ultra-light copper oxide catalyst with a density of 0.58 g / cm 3 , copper oxide content is 30.8wt%, zinc oxide content is 6.8wt%, and specific surface area is 148m 2 / g.
[0068] Example 3
[0069] (1) Powdered phenolic resin and curing agent hexamethylenetetramine are fully mixed with a high-speed stirrer, and the weight ratio of hexamethylenetetramine to phenolic resin is 12 / 100; 125 g of the mixture is fully mixed with 38 g of basic copper carbonate and 5 g of zinc carbonate mixture with a high-speed stirrer;
[0070] (2) raising the temperature of the tablet press to 90° C., placing the above materials into a mold and performing molding on the tablet press to form a 2 mm thick sheet; raising the temperature of the tablet press to 150° C., placing the formed sheet into the mold again and curing it under a pressure of 5 MPa on the tablet press for 10 min; cutting the cured 2 mm thick sheet into 3-5 mm rectangular small particles to obtain a catalyst precursor;
[0071] (3) 100 mL of small particle catalyst precursor was measured and carbonized in a tubular high temperature electric furnace at a heating rate of 10 °C / min and a furnace temperature of 600 °C for 4 hours under nitrogen protection at a flow rate of 200 mL / min. After cooling under nitrogen protection, an ultra-light copper oxide catalyst with a density of 0.65 g / cm 3 , copper oxide content is 35wt%, zinc oxide content is 8.2wt%, specific surface area is 142m 2 / g.
[0072] Example 4
[0073] (1) Powdered phenolic resin and curing agent hexamethylenetetramine are fully mixed with a high-speed stirrer, and the weight ratio of hexamethylenetetramine to phenolic resin is 12 / 100; 125 g of the mixture is fully mixed with 45 g of basic copper carbonate and 25 g of zinc carbonate mixture with a high-speed stirrer;
[0074] (2) raising the temperature of the tablet press to 90° C., placing the above materials into a mold and performing molding on the tablet press to form a 2 mm thick sheet; raising the temperature of the tablet press to 150° C., placing the formed sheet into the mold again and curing it under a pressure of 5 MPa on the tablet press for 10 min; cutting the cured 2 mm thick sheet into 3-5 mm rectangular small particles to obtain a catalyst precursor;
[0075] (3) 100 mL of the small particle catalyst precursor was taken and carbonized in a tubular high temperature electric furnace at a heating rate of 10 °C / min and a furnace temperature of 600 °C for 3 hours. The nitrogen protection was at a flow rate of 200 mL / min. After cooling under nitrogen protection, an ultra-light copper oxide catalyst with a density of 0.78 g / cm 3 , copper oxide content is 30.0wt%, zinc oxide content is 29.5wt%, specific surface area is 153m 2 / g.
[0076] Comparative Example 1
[0077] The CuO / ZnO catalyst was prepared according to the method in Chinese invention patent CN101642707A.
[0078] The specific preparation method is:
[0079] 226ml 1mol / L Cu(NO3)2 solution and 516mL 1mol / L Zn(NO3)2 solution were mixed evenly, and 1000mL 1mol / L Na2CO3 solution was added dropwise to the mixed solution for precipitation, the precipitation temperature was 80℃, and the pH value was controlled at 9.5±0.5. Aging was performed for 2 hours under stirring, the aging temperature was 80℃, and the filter was washed with deionized water, dried at 110℃ for 12 hours, and then calcined at 400℃ for 6 hours before tableting. The content of copper oxide was about 30.2wt%. The content of zinc oxide was 69.8wt%, and the density was 1.5g / cm 3 ,, the specific surface area is 39.5m 2 / g.
[0080] Comparative Example 2
[0081] (1) 100 parts by weight of liquid epoxy resin (Baling Petrochemical, CYD-128), 85 parts by weight of curing agent methyltetrahydrophthalic anhydride (MeTHPA) (Guangdong Shengshida Science and Trade Co., Ltd.), and 1.5 parts by weight of curing accelerator triethanolamine (TEA) (Tianjin Chemical Reagent Factory No. 1) were stirred evenly.
[0082] (2) Weigh 40 g of the epoxy system prepared in step (1) and 180 g of copper-aluminum alloy powder, wherein the copper-aluminum alloy has a Cu content of 50% (by weight) and an aluminum content of 50% (by weight), add an appropriate amount of the mixture into a cylindrical mold, and press the mixture using a flat plate vulcanizer at a temperature of 120° C. and a pressure of 7 MPa for 30 mins, and then press the mixture using a flat plate vulcanizer at a temperature of 150° C. and a pressure of 7 MPa for 90 mins, cool and take out to obtain a granular catalyst precursor;
[0083] (3) 100 mL of the catalyst precursor was measured and placed in a tubular high-temperature electric furnace, with a heating rate of 10° C. / min and a carbonization temperature of 600° C. maintained for 3 hours under nitrogen protection at a nitrogen flow rate of 200 mL / min. After cooling under nitrogen protection, the carbonized catalyst precursor was obtained;
[0084] (4) Prepare 400g of 20% NaOH aqueous solution with deionized water, add the carbonized catalyst precursor obtained in step (3), maintain the temperature at 85°C, filter out the solution after 4 hours, and obtain a composite skeleton copper precursor, wherein the copper metal content is 60% (weight) of the composite skeleton copper precursor. Wash the composite skeleton copper precursor until it is close to neutral, and then place it in a methane fluorine furnace and heat it in an air atmosphere, maintain the temperature at 90 degrees, and keep it warm for 12 hours. The copper oxide content is 35wt% of the composite copper oxide catalyst, and the density is 0.85g / cm 3 Specific surface area is 89.8m 2 / g.
[0085] The catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were tested for carbon monoxide removal, as follows:
[0086] Carbon monoxide removal test:
[0087] Catalyst evaluation was carried out in a fixed bed continuous flow tubular reactor. The catalyst loading was 20 mL. After the catalyst was loaded, it was purged with air at 120°C for 12 hours. The material was a mixed gas of high-purity N2 and CO, and the mixed gas contained 2.2 ppm of CO. The reaction pressure was 3.5 MPa, the reaction temperatures were 50°C and 90°C, and the space velocity was 5000 hr -1 .
[0088] The raw materials and products were detected by gas chromatography Agilent 7890 with a nickel methanogen converter, a thermal conductivity detector and a hydrogen flame detector, with the minimum detection limit of carbon monoxide being 0.1 ppm, and by a trace carbon monoxide analyzer from AMETEK, with the minimum detection limit of carbon monoxide being 1 ppb.
[0089] The reaction was allowed to stabilize for about 10 to 20 hours and the test data were obtained and listed in Tables 1 and 2, where:
[0090] Table 1 shows the reaction conditions of Examples 1 to 4 and Comparative Examples 1 to 2 at a reaction temperature of 50°C, a reaction pressure of 3.5 MPa, and a space velocity of 5000 hr. -1 , the inlet is a mixed gas containing 2.2ppm of CO, and the outlet CO concentration is measured;
[0091] Table 2 shows the reaction conditions of Examples 1 to 4 and Comparative Examples 1 to 2 at a reaction temperature of 90°C, a reaction pressure of 3.5 MPa, and a space velocity of 5000 hr. -1 , the inlet is a mixed gas containing 2.2ppm of CO, and the outlet CO concentration is measured.
[0092] Table 1
[0093]
[0094] Table 2
[0095]
[0096] It can be seen from the data in Table 1 that under the reaction condition of 50°C, the catalysts prepared in Examples 1 to 4 remove CO to 35 to 55 ppb, while the catalysts prepared in Comparative Examples 1 to 2 remove CO to 956 ppb and 780 ppb, respectively, which is an order of magnitude difference.
[0097] It can be seen from the data in Table 2 that under the reaction condition of 90°C, the catalysts prepared in Examples 1 to 4 removed CO to 5.5 to 16 ppb, both lower than 20 ppb, while the catalysts prepared in Comparative Examples 1 to 2 removed CO to 80 ppb and 24.8 ppb, respectively, which still had a large gap.
[0098] The copper oxide contents of Examples 1 to 4 and Comparative Examples 1 to 2 are comparable, and their activities can be compared. From the data in Tables 1 to 2, it can be seen that the activities of the catalysts 1 to 4 prepared by the present invention are significantly higher than the activities of the catalysts prepared by the prior art represented by Comparative Examples 1 to 2, and at a relatively low temperature (such as 50° C. in Table 1), the catalysts prepared by Examples 1 to 4 still have good CO removal capabilities, which indicates that the catalysts prepared by the present invention improve the utilization rate of copper oxide and allow more copper oxide nanoparticles to participate in the catalytic oxidation reaction of CO.
[0099] The porous copper oxide catalysts prepared in Examples 1 to 4 have a porous structure and a low density, which can reach 0.5 to 0.8 g / cm 3 , while improving the utilization rate of the catalyst, it can effectively reduce the cost of the catalyst, and the preparation method is simple and environmentally friendly.
Claims
1. A porous copper oxide catalyst having a porous structure and a density of 0.5 to 1.5 g / cm 3 , preferably 0.5 to 1.0 g / cm 3 , more preferably 0.5 to 0.8 g / cm 3 The specific surface area of the catalyst is 60 to 180 m 2 / g, preferably 120 to 180 m 2 / g.
2. A method for preparing the porous copper oxide catalyst as claimed in claim 1, comprising the following steps: (1) uniformly mixing a metal salt with a solidification system of a carbonizable organic matter and then solidifying the mixture to obtain a catalyst precursor; The metal includes copper; (2) Under the protection of protective gas, the catalyst precursor obtained in step (1) is carbonized at high temperature to obtain the porous copper oxide catalyst.
3. The method for preparing a porous copper oxide catalyst according to claim 2, characterized in that: Step (1), The mass ratio of the solidification system of the metal salt to the carbonizable organic matter is (0.1-5):1, preferably (0.2-2):1, more preferably (0.2-0.6):1; and / or, The solidification system of the carbonizable organic matter comprises the carbonizable organic matter and an additive.
4. The method for preparing a porous copper oxide catalyst according to claim 2, characterized in that: Step (1), The metal salt is at least one of nitrate, carbonate and bicarbonate; and / or, The metal further comprises at least one of zinc, manganese and magnesium; and / or, The mass of copper accounts for no less than 50% of the total mass of the metal, preferably no less than 60%.
5. The method for preparing a porous copper oxide catalyst according to claim 3, characterized in that: The carbonizable organic matter is at least one of epoxy resin, phenolic resin, furan resin, polystyrene, polyacrylonitrile, starch, viscose fiber, lignin, cellulose, styrene-butadiene rubber, and polyurethane rubber; and / or, The additives include a curing agent, and preferably also include at least one of a curing accelerator, a dye, a colorant, an antioxidant, a stabilizer, a plasticizer, a lubricant, a flow modifier, a flame retardant, an anti-drip agent, an anti-caking agent, an adhesion promoter, a conductive agent, an impact modifier, a demoulding aid, and a nucleating agent.
6. The method for preparing a porous copper oxide catalyst according to claim 2, characterized in that: Step (2), The protective gas is at least one of nitrogen and an inert gas; the inert gas is preferably argon; and / or, The carbonization temperature is 400 to 1200° C., preferably 400 to 700° C., more preferably 550 to 700° C.; and / or, The carbonization time is 1 to 10 hours, preferably 2 to 6 hours, and more preferably 2 to 4 hours.
7. A porous copper oxide catalyst obtained by the preparation method according to any one of claims 2 to 6.
8. Use of the porous copper oxide catalyst as claimed in claim 1 or 7 in a reaction for removing trace amounts of CO.
9. Use of the porous copper oxide catalyst as claimed in claim 8 in the reaction of removing trace CO in materials, characterized in that: The CO content in the material is 0.01 to 1000 ppm, preferably 0.01 to 100 ppm, more preferably 0.01 to 10 ppm, most preferably 0.1 to 5 ppm; and / or, The reaction temperature is 0 to 150°C, preferably 20 to 120°C; and / or, The reaction pressure is 0.1 to 5 MPa, preferably 0.1 to 3.5 MPa; and / or, The volume space velocity during gas phase reaction is 100~10000h -1 and / or, The volume space velocity during liquid phase reaction is 0.5~100h -1 .
10. Use of the porous copper oxide catalyst according to claim 8 in a reaction for removing trace amounts of CO, characterized in that: The material is at least one of α-olefins, saturated hydrocarbons, styrene, and other materials; preferably at least one of liquid materials of propylene, 1,3-butadiene, 1-butene, and 2-butene, or at least one of gaseous ethylene, gaseous propylene, hydrogen, nitrogen, oxygen, air, and inert gas.
Citation Information
Patent Citations
Bi-component copper-zirconium catalyst for deeply removing CO
CN101642707A
Composite copper oxide catalyst for trace CO removal, preparation method and applications thereof
CN105396587A
Cu catalyst based on metal organic framework, preparation method and application
CN105664944A
CuOx catalyst, preparation method of catalyst and application of catalyst in prevention and control of environmental pollution
CN106423164A
Method for preparing silver carbonized Raney copper catalyst, catalyst and application
CN107952450A